1986
DOI: 10.1042/bj2340233
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of pyruvate dehydrogenase kinase activity in cultured hepatocytes by glucagon and n-octanoate

Abstract: The activity of pyruvate dehydrogenase kinase in extracts of mitochondria from rat hepatocytes cultured for 21 h in medium 199 was increased 2.5-fold by the presence of 55 nM-glucagon and 1 mM-sodium n-octanoate in the culture medium. The change was comparable with that induced in vivo by 48 h starvation. The potential contribution of branched-chain complex to estimates of PDH-complex activity in rat liver mitochondria has been defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
62
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 19 publications
5
62
1
Order By: Relevance
“…The stable enhancement of its activity has been variously attributed to increased specific activity of PDHK [8] or to increased enzyme concentration [9]. The PDHK activity enhancement elicited by starvation can be reproduced over a similar timescale (21-24 h) by the addition of glucagon and a fatty acid (n-octanoate) in cultured hepatocytes [10][11][12]. As the increase in hepatocyte PDHK activity in culture is comparable with that of starvation in i o [10], it has been suggested that increased fatty acid oxidation rates and cAMP concentrations mediate the response to starvation [3].…”
Section: Introductionmentioning
confidence: 73%
See 4 more Smart Citations
“…The stable enhancement of its activity has been variously attributed to increased specific activity of PDHK [8] or to increased enzyme concentration [9]. The PDHK activity enhancement elicited by starvation can be reproduced over a similar timescale (21-24 h) by the addition of glucagon and a fatty acid (n-octanoate) in cultured hepatocytes [10][11][12]. As the increase in hepatocyte PDHK activity in culture is comparable with that of starvation in i o [10], it has been suggested that increased fatty acid oxidation rates and cAMP concentrations mediate the response to starvation [3].…”
Section: Introductionmentioning
confidence: 73%
“…The PDHK activity enhancement elicited by starvation can be reproduced over a similar timescale (21-24 h) by the addition of glucagon and a fatty acid (n-octanoate) in cultured hepatocytes [10][11][12]. As the increase in hepatocyte PDHK activity in culture is comparable with that of starvation in i o [10], it has been suggested that increased fatty acid oxidation rates and cAMP concentrations mediate the response to starvation [3]. The effect of starvation for 48 h is reversed within 4-8 h of refeeding [6], over which period hepatic cAMP concentrations decline [13] and fatty acid oxidation is suppressed [14].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations